EVALUASI PENGENDALIAN INTERN TERHADAP MUTASI BARANG JAMINAN DI GUDANG SEBAGAI ALAT UNTUK MENGHINDARI KECURANGAN PADA PERUM PEGADAIAN SIDOARJO - Totok Mardianto (Media Mahardhika, 2020)
Internal cotrol structures contain control risks. One of these limitations is the human factor that exists in control procedures The effectiveness of certain controls can be lost because employees misunderstand instructions, inaccuracy, absence and collusion between employees or with outsiders. The second limitation is that control cannot cover all transactions, for example control is not applied to transactions that are not routine such as the cessation of executives or important personnel or the use of computers will affect and require modifications to the existing control structure. If a company is found to have implemented a system that deviates from the procedure, a test will be conducted to determine the cause of the deviation. With the control system of the procedures used, the deviation will be made improvements and ways of sloving the problems faced. One of the problems regarding the implementation of internal control procedures regarding the transfer of collateral items in warehouses as a tool to avoid fraud at the Sidoarjo Public Corporation Pawnshop. The technique uded in this study is a method based on research conducted directly or data obtained from within the company its elf. Data collection techniques by conducting observation, documentation, and interviews. To test the data obtained using descriptive analysis and comparative analysis. Data that has fulfilled the test results in collateral management and collateral inspection as aform of control over collateral entering the warehouse. There is a recording and division of classes in order to facilitate warehouse officers/authorities in carrying out the inspection of collateral items and warehouse books as the warehouse staff's responsibility for warehouse management in Sidoarjo Public Corporation.